Analysis of the Influence of Institutional Dynamics on Juvenile Criminality in Nakuru Sub-County, Kenya - Kiche, Justus O. (2020)
The present study was prompted by the observation that there was very high prevalence of juvenile criminality in Kenya. This study focused on analyzing the influence of institutional dynamics on juvenile criminality in Nakuru sub-county, Kenya. The target population for the study was 144 that included 73 police officers from Bondeni police station, 35 juveniles drawn from children remand home, 35 parents/guardians of the said juveniles, and 1 chief from Bondeni location. The researcher selected a sample size of 102 respondents composed of 62 police officers, 32 juveniles, 7 parents/guardians, and 1 chief. The researcher used a questionnaire and an interview schedule to collect views. The validity of this study was achieved through a thorough consultation with the supervisors and other specialist. Reliability was used to focus on the degree to which empirical indicators are stable and consistent. A Cronbach’s coefficient alpha was used to measure the reliability of the research instruments. An alpha coefficient value of 0.6 suggested the instrument is reliable. The study adopted the mixed research methodology and the concurrent triangulation design. Quantitative data was analyzed descriptively and inferentially while qualitative data was analyzed thematically. The study found out that there was an important positive association between all the measures of institutional dynamics and juvenile criminality in Nakuru sub-county. The study concluded that there was an influence of institutional dynamics and juvenile criminality in Nakuru sub-county, Kenya. The study recommends that the government should make efforts in making families functional in order to reduce juvenile criminality. There is therefore need for juvenile department to improve on their policies and expected performance in regard to juvenile criminality. Keywords: Kenya, Nakuru, Biological dynamics, crime, doliincapax, economic dynamics, government dynamics, juvenile, social dynamics, urban. DOI: 10.7176/JLPG/97-07 Publication date:May 31st 202